A clinical study of effects of pregnancy on diseases like painful crisis, seizure disorders, hepatopathy, acute anemia and its outcome - Sitalakshmi, V.; ., Narmada; ., Kavitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The ability of the blood cells to carry oxygen is especially important in pregnancy. Anemia may result in lower amount of oxygen going to the fetus and slowed fetal growth. Because it affects so many organs and body systems, women with the disease are more likely to have complications in pregnancy. The main objective was to study the effects of pregnancy on disease and its outcomes. Methods: It is a hospital based prospective study. The study was conducted at Narayana Medical College Nellore, Andhra Pradesh. The patients admitted in Obstetrics and Gynecology Department were included in the study. The study included total of 45 patients. Detailed history included age, socioeconomic status, address, education and occupation of the patient’s Permission from Institutional Ethics Committee was obtained. Results: Maximum patients were gravida 2-3, and minimum were gravida 4 or more. Maximum numbers of patients were in group 20-25. The patients with preterm birth that is delivery before 37 weeks of pregnancy were 15. Low birth weights were 20 and of still birth and new born death was 4. Conclusions: The present study was carried out in 45 cases and appropriate prenatal care and careful monitoring throughout pregnancy, can have healthy pregnancy with significant improvement in pregnancy outcome.